P353 Agreement between patients, senior and junior physicians on disease activity and burden scoring in inflammatory bowel disease, using a tele-monitoring platform. (21st January 2022) - Mangia, M; Giuffrida, E; Figini, V; Colombo, A; Carli, E; Mendolaro, M; Lavagna, A; Lia, C; Bonina, M; Martínez De Carnero, F; Morello, E; Cosimato, M; et al.
Abstract: Background: Inflammatory bowel disease (IBD) are complex chronic disabling disease with variable disease activity. Physicians' and patients' perception of disease burden may vary considerably. The use of eHealth tools is a useful technique to monitor disease burden, but physicians- and patients-reported disease measurement do not overlap completely. Aim of this study was to perspectively explore agreement for rating disease activity and impact between patients, senior (consultants) and junior (residents) physicians. Methods: Using a tele-monitoring platform ( IBD Tool ), 508 consecutive IBD patients filled disease activity (Harvey Bradshaw Index, HBI, for Crohn's and Patient Simple Clinical Colitis Activity Index, P-SCCAI, as appropriate) and disease impact (Pictorial Representation of Illness and Self-Measure, PRISM ) validated questionnaires at the time of outpatient visits. At the same timepoint also senior and junior physicians filled the same activity ( HBI and Clinician SCCA, C-SCCAI ) and impact ( PRISM ) questionnaires. Agreement between patients' and physicians' scores was analysed with intraclass and concordance correlation coefficients and Spearman's rank correlation coefficient. Results: A total of, 629 filled questionnaires regarding, 508 patients was available for analysis. Crohn's patients were, 52%, and females were, 50%, median age of patients was, 44 years, and their median age at diagnosis was, 28 years, while median disease duration was, 12 years; overall, 39% of patients underwent surgery before being enrolled. Agreement for different scores among patients, senior and junior physicians was always significant and details are reported in Table, 1 . Table, 1. Agreement among patients, senior and junior physicians for HBI, SCCAI and PRISM. A closer inverse relationship between activity indices and PRISM was found in physicians' scores, while it was looser in patients' scores. Senior physicians' agreement was -0.774 and -0.793 for HBI and C-SCCAI, respectively, to PRISM (p<0.0001); Junior physicians' agreement was -0.745 and -0.753 for HBI and C-SCCAI, respectively, to PRISM (p<0.0001); patients' agreement was -0.414 and -0.498 for HBI and C-SCCAI, respectively, to PRISM (p<0.0001). Conclusion: Agreement of patients' and physicians' scoring of disease activity on a tele-monitoring platform is good and significant, and it is optimal between junior and senior doctors. According to published data, physicians' and patients' agreement regarding the perception of disease impact on patients' lives (measured with PRIMS) is slightly worse, although still significant, while it is good comparing junior and senior physicians' rates. When exploring relationships between PRISM and disease activity scores it is good for physicians, and only average for patients.